Development and implementation of a training programme to improve implementation of the nursing process in public hospitals of Limpopo Province, South Africa - Mutshatshi, Takalani Edith (My University, 2021)
The purpose of this study was to develop and implement a training programme to improve the implementation of the nursing process in public hospitals in the Limpopo Province, South Africa. A mixed-method convergent parallel design was used in this study. Qualitative data were collected from 18 professional nurses using a semi structured one-to-one interview using an interview guide. The quantitative data were collected from 283 professional nurses through a self-administered questionnaire. Qualitative data were analysed using Tesch’s open coding method while quantitative data were analysed using Statistical Package for Social Sciences (SPSS) version 24. The findings were merged using a joint display to determine the extent to which the two data confirm, contradict, or expand. The study was guided by Dickoff, James, and Wiedenbach's Practice Orientated theory and Knowles Adult learning theory. The findings revealed that professional nurses perform their activities following the steps of the nursing process, nurses can implement the nursing process timeously but have problems with some steps of the nursing process. Nurses know the importance of recording but the incomplete recording was found to be a challenge, nurses were not attending in-service training on the nursing process leading to poor implementation of the steps, there were inadequate human and material resources, poor management and administrative support affecting the implementation of the nursing process, nurses do not know about the staff training and development policy and there is no training programme on the nursing process in the hospitals. The study, therefore, recommends that the nursing management support for nurses implementing nursing process; provision of adequate human and material resources; scheduling of continuous in-service training sessions for all categories of nurses; adoption of the short training course developed by the Department of Health in the Limpopo Province for in-servicing professional nurses; nursing process be introduced from the first level of nursing training and be reinforced throughout training; the short course should be included in the curriculum of all undergraduate nurse training, and other researchers to develop a model for effective implementation of the nursing process
Thesis (Ph.D.(Nursing Science)) -- University of Limpopo, 2021
Keywords: Nursing process; Implementation; Professional nurse; Public hospital; Training programme; Experiential learning; Nursing process; Nursing